2009
DOI: 10.1677/joe-08-0476
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of testosterone-induced muscle fiber hypertrophy: involvement of p38 mitogen-activated protein kinase-mediated Notch signaling

Abstract: As a prerequisite for studies using mutant mice, we established a mouse model for investigating the molecular mechanisms by which testosterone (T) promotes muscle growth. Groups of six adult male mice (C57BL/6) received one of the following treatments: 1) vehicle (sterile distilled water; normal control) and 2) GnRH antagonist with empty (sham control) or 2 cm T-filled implant. Mice were killed 2, 6, and 8 weeks after treatment. T treatment for 8 weeks resulted in a significant (P<0.001) increase in fiber area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
(41 reference statements)
0
38
0
Order By: Relevance
“…Satellite cell activity can be measured by two markers: proliferating cell nuclear antigen (PCNA), an immunohistochemical marker of entry into the cell cycle, and myogenin, a myogenic regulatory factor (MRF) that regulates terminal differentiation of myoblasts into myotubes and myofibers , Chen et al 2005, Dubois et al 2012. These findings of PNCAC and myogeninC satellite cells, along with findings of an increased expression of notch, a key signaling molecule in satellite cell proliferation, give weight to the hypothesis that testosterone exerts its anabolic effects by promoting satellite cell replication and activation, resulting in an increased number of myogenically committed satellite cells , Sinha-Hikim et al 2006, Brown et al 2009). In addition to an increased number and activity of satellite cells, ultrastructural changes within the satellite cells themselves have been noted, such as increased mean cell area and mean mitochondrial area, a decreased nuclearcytoplasmic ratio and structural changes including a larger amount of endoplasmic reticulum and more pinocytic vesicles , Herbst & Bhasin 2004.…”
Section: Effects Of Testosterone Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite cell activity can be measured by two markers: proliferating cell nuclear antigen (PCNA), an immunohistochemical marker of entry into the cell cycle, and myogenin, a myogenic regulatory factor (MRF) that regulates terminal differentiation of myoblasts into myotubes and myofibers , Chen et al 2005, Dubois et al 2012. These findings of PNCAC and myogeninC satellite cells, along with findings of an increased expression of notch, a key signaling molecule in satellite cell proliferation, give weight to the hypothesis that testosterone exerts its anabolic effects by promoting satellite cell replication and activation, resulting in an increased number of myogenically committed satellite cells , Sinha-Hikim et al 2006, Brown et al 2009). In addition to an increased number and activity of satellite cells, ultrastructural changes within the satellite cells themselves have been noted, such as increased mean cell area and mean mitochondrial area, a decreased nuclearcytoplasmic ratio and structural changes including a larger amount of endoplasmic reticulum and more pinocytic vesicles , Herbst & Bhasin 2004.…”
Section: Effects Of Testosterone Administrationmentioning
confidence: 99%
“…Notch signaling is essential for satellite cell proliferation and myogenic progression and may be part of the mechanism of satellite cell activation via testosterone (Sinha-Hikim et al 2006). Notch expression has been demonstrated to increase after testosterone administration; however, it is unclear whether this is a direct effect or the result of partial regulation by other elements of the skeletal muscle metabolism cascade (Sinha-Hikim et al 2006, Brown et al 2009, Dubois et al 2012). …”
Section: Enhancement Of Notch Signalingmentioning
confidence: 99%
“…Activation of p38 MAPK and JNK in muscle lysates was measured by TiterZyme EIA kit (Assay Designs Inc., Ann Arbor, MI), as described previously by us (19,28).…”
Section: Measurements Of Kinase Activationmentioning
confidence: 99%
“…Recently we have shown that the inactivation of c-jun NH 2 -terminal kinase (JNK) together with the activation of p38 MAPK is critical for testosterone-induced activation of Notch signaling and, consequently, induction of muscle fiber hypertrophy in young mice (19). Given that JNK signaling constitutes a critical component of apoptotic signaling in skeletal muscles after injury (20) and in aging (13), it is possible that testosterone-mediated inhibition of JNK could lead to suppression of muscle cell apoptosis and cause fiber growth.…”
mentioning
confidence: 99%
“…Although a relationship between p38-MAPK and NOTCH has previously been suggested, mechanistic details were not clearly established (Brown et al, 2009;Gonsalves and Weisblat, 2007;Kiec-Wilk et al, 2010;Park et al, 2009). We found that the full ability of p38-MAPK to induce NOTCH3 is dependent on MYC.…”
Section: Transcriptional Regulation Of Notch3 By P38-mapkmentioning
confidence: 44%